Put a Ring on it! Why We Need More Commitment in Media Scholarship - Freedman, Des (Javnost-The Public, 2017)
This article reflects on how academics might best respond to the social, political and economic crises that are unfolding in the contemporary world: for example, increased inequality within nations, falling levels of trust in established political institutions, the growth of populist movements that seek to use racism and sexism to divide populations and the failure of the media to scrutinise successfully current dangers. In particular, in light of intensified marketisation of and managerialism within higher education, the article asks how communication scholars should respond to a situation in which the media are seen as intimately connected to both the emergence of and solution to these crises. To what extent should academics remain aloof from grassroots movements or should their research and teaching inform campaigns for social justice? The article discusses how academics are simultaneously urged to “engage” in the social world in order to achieve “impact” and to retain a scholarly detachment that protects their “neutrality”. It argues that media studies, however, should not (and probably cannot) be insulated from fundamental questions of power and injustice, and suggests that academics should refuse the false binary between “scholarly” and “political” activity to pursue a “committed” approach to their work.